Observer Based Single-Phase Active Current Harmonic Filter for Distributed Industrial Loads - Patel, Hanuman; Mathur, Sanjay Kumar; Rajpurohit, Vikram Singh (Asian Journal of Electrical Sciences, 2022)
Harmonic currents are introduced into power system as use of nonlinear electrical loads increases. Extra losses are caused by harmonic current stream into effective supply lines. A dynamic power filter engenders harmonic compensating current using a switching inverter. Single-phase current into the harmonic filter connects in parallel to load end and inject current harmonic required by the load feeder to avoid harmonic current in the direction of power system. This report discusses harmonic problem, available harmonic mitigation techniques, basic design of filter, control strategy, design steps of major hardware blocks, modelling and simulation of current harmonic filter in MATLAB SIMULINK setting, component selection, hardware implementation and final results. This filter will eliminate harmonic up to 45th order. The control circuit consists of a peak filter, all-pass filter, low pass filter and adders which are used to produce error signal by comparing harmonic current demand of load and injected harmonic current through switching inductor.